Research hotspots and trends in the application of diffusion tensor imaging in ischemic stroke: a bibliometric analysis (2003–2024) - Chen, Xu; Liu, Meifang; Yang, Xiaolin; Yue, Mengqi; Yu, Haocheng; Wang, Haiqiang; Wang, Zirong; Shi, Jing; Qiu, Yong (Frontiers in Neurology, 2025)
BackgroundIschemic stroke (IS) is a limited ischemic necrosis or softening of brain tissue caused by impaired blood supply to the brain, ischemia, and hypoxia, ultimately leading to various neurological dysfunctions. In recent years, with the continuous development of imaging technology, diffusion tensor imaging (DTI) has made many advances in the field of IS. However, bibliometric analysis in this field is still lacking. This study aims to investigate the present status of study progress, research hotspots, and possible research trends in the application of DTI in IS through bibliometric analysis methods.MethodsThe Web of Science Core Collection (WoSCC) database was searched for relevant literature on DTI in IS from 2003 to 2024. Using VOSviewer, CiteSpace, and R package Bibliometrix to visualize and analyze countries, publications, authors, co-citations, and keywords.ResultsA total of 493 papers from 45 countries were incorporated. The number of DTI-related publications in IS has been increasing year by year. The three primary publishing nations are the United States, China, and the United Kingdom. Harvard University is the research institution with the most extensive of publications. STROKE is the most contributing and cited journal in the field. Markus, Hugh S is the author with the highest number of publications. Thomalla, G. is the author with the highest number of citations. The analysis of keywords and co-cited literature can suggest the primary research directions and trends in the field containing diffusion tensor imaging, ischemic stroke, white matter (WM), Wallerian degeneration (WD), corticospinal tract (CST), fractional anisotropy (FA), recovery and biomarker for motor function.ConclusionAccording to the bibliometric study's findings, this area is progressively gaining the attention of researchers and may become a research hotspot in IS. However, the current study still needs to strengthen cross-regional cooperation, and higher quality and broader research is still necessary to lay the foundation for reaching the consensus of various experts.